PERAN STRATEGIS PENYULUH SWADAYA DALAM PARADIGMA BARU PENYULUHAN PERTANIAN INDONESIA (Forum Penelitian Agro Ekonomi, 2021)
Involvement of farmers as actors to support extension activities have been underway for a long time with various approaches. In Indonesia, it started from the involvement of Kontak Tani (Advanced Farmers) in Supra Insus era, then farmer to farmer extension at P4S, as well as Penyuluh Swakarsa (Independent Extension Workers)” (in 2004), and the latest is Penyuluh Swadaya (Self-Help Agricultural Extension Workers) since 2008. The existence of self-help farmer extension workers are recognized since the enactment of Law No. 16/2006 on Extension System of Agricultural, Forestry and Fisheries. However, even though it runs nearly 10 years, the development of the role of self-help farmer extension workers is not optimal. This paper is a review of various posts including the recent research on self-help farmer extension workers and it aims to study the potential and problems of self-help farmer extension workers. It shows that the self-help farmer extension workers have a self-help capabilities and distinctive social position and they have to get right role. Appropriate support should be given to self-help farmer extension workers as the agricultural extension worker in the future and it must be distinguished between the government and private extension workers.
Keywords: agricultural extension; new paradigm of agricultural extension; self-help farmer extension worker